Hubungan Status Pekerjaan dengan Keaktifan Kunjungan Ibu dalam Posyandu di Posyandu X Surabaya - Meivy Isnoviana; Jesica Yudit (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2020)
Posyandu is a Community-Based Health Effort (UKBM) which is managed, administered and designated by the community. It will monitor the growth and development of toddlers every month. In the posyandu Surabaya in 2018, only about 36.75% of toddlers was weighed which is below the indicator of the coverage by Government as 85%. The purpose of this study was to find out the relationship of working status with the mother’s activity to visit in posyandu at Posyandu X Surabaya. The study design was observational analytic with a cross sectional approach. The population were mothers with toddlers aged 0 - 59 months who reside in the area of Posyandu with a sample size of 91 respondents taken by purposive sampling. Data collection using questionnaire sheets. Data were analyzed by the Spearman rank test (α = 0.05). The results of the study showed that the majority of toddlers in the Posyandu area (47.3%) were not working mothers and the activeness of visits to the posyandu were rare (50.5%). Spearman rank statistical test results obtained p value = 0,000 and r = 0.465 means that there is a correlation between working status and the mother’s activity of visits in Posyandu activity at Posyandu X Surabaya. It can be concluded that working mothers do not have free time to visit posyandu compared to mothers who do not work